Consequences of a Delayed Diagnosis of Kaposi's Sarcoma: A Case Report of Disseminated Infection - Leonardo Henrique Bertolucci; Carolina Rossatto Ribas; Ellen Mullich Flesch; Lisiane Aurélio Knebel Balbinot; Fabiano Ramos (MDPI AG, 2021)
Kaposi's Sarcoma (KS), first reported by Dr [...]